2013
DOI: 10.1080/10640266.2013.741988
|View full text |Cite
|
Sign up to set email alerts
|

Teasing and Disordered Eating Behaviors in Spanish Adolescents

Abstract: The purpose of this study is to investigate the associations between peer teasing and body dissatisfaction (BD), emotional symptoms, drive for thinness (DT), and abnormal eating behaviors, as well as to analyze the mediating role of gender and body mass index (BMI) in such disorders. We screened 57,997 school children between 13 and 16 years of age. Scores in weight-related teasing and competency-related teasing were higher among girls, as well as overweight or obese individuals. Weight-teasing correlated more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
4
11
2
5
Order By: Relevance
“…Previous studies in the United States have found that peers and family members are a common source of appearance‐ and weight‐related teasing, with parents—especially the father—encouraging overweight children to control their weight . In addition, several studies in Western countries have found that overweight adolescents are more likely to be victims of weight teasing . Taken together, these findings seem to confirm the idea that stigmatization of overweight adolescents is a widespread problem .…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Previous studies in the United States have found that peers and family members are a common source of appearance‐ and weight‐related teasing, with parents—especially the father—encouraging overweight children to control their weight . In addition, several studies in Western countries have found that overweight adolescents are more likely to be victims of weight teasing . Taken together, these findings seem to confirm the idea that stigmatization of overweight adolescents is a widespread problem .…”
Section: Discussionsupporting
confidence: 69%
“…39 When it comes to teasing about weight, it seems that adolescent girls are more likely to report being teased than boys, a finding observed in Western countries such as the United States and Spain. 38,40,41 Although in our results more boys than girls reported weight teasing, these sex differences disappeared when the analyses were adjusted by weight status. Therefore, independently of sex, the frequency of body-related teasing in both sexes reinforce the idea that the Czech Republic is adopting societal standards of Western countries, 42 emphasizing weight as a central component of physical appearance.…”
Section: Sex Differencescontrasting
confidence: 77%
See 2 more Smart Citations
“…These patterns also appear to be present in minority samples of youths. In a study of 57,997 Spanish adolescents, weight-related teasing was significantly related to abnormal eating in girls and with body dissatisfaction in both boys and girls [16]. Among Hispanic and African American girls (N=141), weight-related teasing from peers and parents correlated with emotional eating, and parent-specific teasing was associated with binge eating [17].…”
Section: Weight Stigma and Associated Health Consequences Binge Eatingmentioning
confidence: 98%